Relations between anger and DSM-5 posttraumatic stress disorder symptoms. (30th October 2016) - Durham, Tory A.; Byllesby, Brianna M.; Armour, Cherie; Forbes, David; Elhai, Jon D.
Abstract: The present study investigated the relationship between posttraumatic stress disorder (PTSD) and anger. Anger co-occurring with PTSD is found to have a severe effect across a wide range of traumatic experiences, making this an important relationship to examine. The present study utilized data regarding dimensions of PTSD symptoms and anger collected from a non-clinical sample of 247 trauma-exposed participants. Confirmatory factor analysis (CFA) was used to determine the underlying factor structure of both PTSD and anger by examining anger in the context of three models of PTSD. Results indicate that a five-factor representation of PTSD and one-factor representation of anger fit the data best. Additionally, anger demonstrated a strong relationship with the dysphoric arousal and negative alterations in cognitions and mood (NACM) factors; and dysphoric arousal was differentially related to anger. Clinical implications include potential need to reevaluate PTSD's diagnostic symptom structure and highlight the potential need to target and treat comorbid anger in individuals with PTSD. In regard to research, these results support the heterogeneity of PTSD. Highlights: Three competing PTSD models were compared and validated against anger. Results indicated PTSD's dysphoric arousal model fit the data best. Anger demonstrated significant relations with NAMC, dysphoric arousal and anxious arousal. Anger was most related to dysphoric arousal.